Transformation of religious authority in the digital era: A post-normal times analysis by Ziauddin Sardar on the phenomenon of social media da’wah - Rachman, Arief; Saumantri, Theguh; Hidayatulloh, Taufik (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose – This study aims to analyze how digital transformation in Islam has altered the structure of religious authority, using the Post-Normal Times (PNT) approach developed by Ziauddin Sardar. Method – This research employs a qualitative-descriptive approach, analyzing the digital da’wah phenomenon, specifically social media's role in shaping religious authority. Result – The findings indicate that the digitalization of religion has caused a shift in religious authority from the traditional hierarchy dominated by scholars and religious institutions to a popularity-based authority, where figures like celebrity preachers and Islamic influencers have become dominant. Social media facilitates the spread of da’wah, but also gives rise to phenomena such as instant fatwas, fragmentation of religious teachings, and the commodification of religion. In the Post-Normal Times framework, the uncertainty of authority increases, where algorithms and popularity replace traditional scholarly credibility. Implication – This study has significant implications for managing digital da’wah, religious literacy, and the need for regulation to minimize negative impacts, such as spreading misinformation and oversimplifying religious teachings. Originality/Value – This study offers an original contribution by applying the Post-Normal Times theory to analyze changes in religious authority within the context of digital da’wah, a topic not widely discussed in the literature on religion and social media. *** Tujuan - Studi ini bertujuan untuk menganalisis bagaimana transformasi digital dalam Islam telah mengubah struktur otoritas agama, menggunakan pendekatan Post-Normal Times (PNT) yang dikembangkan oleh Ziauddin Sardar. Metode - Penelitian ini menggunakan pendekatan kualitatif-deskriptif, menganalisis fenomena da’wah digital, khususnya peran media sosial dalam membentuk otoritas agama. Hasil - Temuan menunjukkan bahwa digitalisasi agama telah menyebabkan pergeseran otoritas agama dari hierarki tradisional yang didominasi oleh ulama dan lembaga agama ke otoritas berbasis popularitas, di mana figur seperti pendakwah selebriti dan influencer Islam menjadi dominan. Media sosial memfasilitasi penyebaran da’wah, tetapi juga menimbulkan fenomena seperti fatwa instan, fragmentasi ajaran agama, dan komodifikasi agama. Dalam kerangka Post-Normal Times, ketidakpastian otoritas meningkat, di mana algoritma dan popularitas menggantikan kredibilitas ulama tradisional. Implikasi – Studi ini memiliki implikasi signifikan dalam mengelola da’wah digital, literasi agama, dan kebutuhan regulasi untuk meminimalkan dampak negatif, seperti penyebaran informasi yang salah dan penyederhanaan berlebihan ajaran agama. Orisinalitas/Nilai – Studi ini memberikan kontribusi asli dengan menerapkan teori Post-Normal Times untuk menganalisis perubahan otoritas agama dalam konteks da’wah digital, topik yang belum banyak dibahas dalam literatur tentang agama dan media sosial.